1990
DOI: 10.3950/jibiinkoka.93.1250
|View full text |Cite
|
Sign up to set email alerts
|

Pathohistological Study on Active Endolymphatic Hydrops in Guinea Pig

Abstract: Recently Meniere's disease is believed to show a pathological features of endolymphatic hydrops, but the etiology of this disease has not yet been ascertained. Many investigators tried to create animal models with endolymphatic hydrops by obliterating endolymphatic sac and duct. However, these methods have not been adequate to explain the mechanism of development of Meniere's disease, because it gives mechanical damage to destroy endolymphatic sac and duct. On the other hand, Meniere's disease is thought to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Emotional stress has been associated with increased frequency and severity of attacks 11 . Animal studies have demonstrated histologic evidence of endolymphatic hydrops in guinea pigs exposed to stress 12 . However, recent findings of elevated levels of cortisol in patients with longer histories of MD as compared with those with shorter histories suggests that stress is likely the result of, and not the cause of, MD 13 .…”
Section: Chronic Managementmentioning
confidence: 99%
“…Emotional stress has been associated with increased frequency and severity of attacks 11 . Animal studies have demonstrated histologic evidence of endolymphatic hydrops in guinea pigs exposed to stress 12 . However, recent findings of elevated levels of cortisol in patients with longer histories of MD as compared with those with shorter histories suggests that stress is likely the result of, and not the cause of, MD 13 .…”
Section: Chronic Managementmentioning
confidence: 99%